Teams Games Tournament (TGT) Learning Model On The Mastery Of Arabic Vocabulary - Lestari, Fratiwi Alya; R, Mantasiah; Bachtiar, Fauziah (Universitas Negeri Makassar, 2024)
Abstract. The purpose of this study was to obtain data on the effectiveness of the Teams Games Tournament (TGT) learning model on the mastery of Arabic vocabulary of 8th grade students of MTs DDI Takkalasi Kab. Barru. This research is a type of Quasi Experiment research. The population of this study were students of class VIII MTs DDI Takkalasi consisting of 3 classes totaling 94 students. The sample was selected using purposive sampling technique, namely class VIII B2 as an experimental class totaling 32 students and class VIII B3 as a control class totaling 32 students. The data of this study were obtained using t-test. The results of data analysis showed that th (4.891) > tt (1.999) at a significant level of 0.05. The results of this study indicate that the Teams Games Tournaments (TGT) learning model is effective on the mastery of Arabic vocabulary of class VIII MTs DDI Takkalasi Kab. Barru.Keyword: Teams Games Tournament (TGT) learning model, Mastery of Arabic vocabulary